A RAPID ASSESSMENT ON VERTEBRATES IN UiTM KUALA PILAH CAMPUS AND ITS ADJACENT FOREST RESERVE, NEGERI SEMBILAN - Manoshini Appanan; Nur Aina Amira Mahyudin; Kaviarasu Munian; Mohammad Shahfiz Azman (Journal of Academia)
During the Forest Biological Diversity Scientific Expedition Programme, a rapid assessment was carried out at the Universiti Teknologi MARA (UiTM) Kuala Pilah Campus in Negeri Sembilan, which is built next to the Pelangai Forest Reserve (PFR). The rapid assessment was executed based on direct observation, animal calling,footprints and mark,and active search around the campus and its adjacent forest. In total, 45 species of vertebrates were recorded based on the two days survey, which includes five speciesof mammals, 32 species of birds, and eight species of herpetofauna. Out of 45 species, only White-handed Gibbon (Hylobates lar) and Javan Myna (Acridotheres javanicus)are categorised as threatened species under IUCN Red List of Threatened Species.In conclusion, this information presented herein should not be treated as exhaustive and more systematic surveys should be carried out to assist the university and forestry department in terms of vertebrates’documentation within their management landscapes.